Produção de conhecimento em biologia com práticas educomunicativas - Ribeiro, Célio Alves (2014)
This paper addresses the Biology of Cognition, recognizing that life is to know, and knowing is live, and supporting it with the construction of knowledge in ontoepistemogênese. The Educational Communication (Media Education) immerses as instructional design supported by the experiences of knowledge by riding lessons, interviews, lectures and research. In this pedagogical concept, students and educators construct meaning from their knowledge in the autonomy of the curriculum reframing, as an active agent within the school disciplinary proceedings. So, how to produce knowledge in biological sciences through educomunicativas practices in interactive networks ecosystems? One should promote learning built the participation and ownership of students in social media, focusing on teaching biology and its relations with the everyday student. It is also necessary to build a Facebook profile for interactivity and sharing of information produced by students and teachers as well as perform exhibition and field classes that the student make the relations of disciplinary knowledge with on-site observations of knowledge in the natural environment. This work, which took place at the School of High School Father Rodolfo F. da Cunha, took a progressive pedagogical trend with liberating and libertarian principles. A qualitative approach was used, with procedures of an action research in that associated with the Focus Group, as data collection technique was held a collective self-reflection of educational practices, as well as the understanding of these practices and situations where such practices happened, collaboratively. Data collection took place in the presence ecosystems and online, with interviews, memos and field notes, which were analyzed, generating readings for the categories of analysis, interpretations and conclusions. The educomunicativas activities and posted on Facebook emerged laden with feelings about the biology of learning in collaborative networks, and the pedagogical processes and environments where these practices occur. Then they also interfere with the learning process. Therefore, it was found that when there is coupling of disciplinary curricular knowledge with local knowledge and tasks, with the educomunicativas teaching practices, and when they occur collaboratively, this knowledge acquire values that are added in the interests of personal and social transformation, in-person demonstrations and online.